Exposure to Intimate Partner Violence Amongst Women of Reproductive Age in Lagos, Nigeria: Prevalence and Predictors - Okenwa, Leah E.; Lawoko, Stephen; Jansson, Bjarne (Journal of Family Violence, 2009)
Research on predictors of Intimate Partner Violence (IPV) in Sub-Saharan Africa is contradictory, necessitating further investigation. This study sought the prevalence and predictors of IPV among women in Lagos, Nigeria. Questionnaire data from 934 women visiting an obstetrics and gynecology clinic in Lagos were analyzed using multivariable methods. The 1 year prevalence of IPV was 29%, with significant proportions reporting psychological (23%), physical (9%) and sexual (8%) abuse. In-access to information, women’s autonomy and contribution to household expenses independently predicted IPV. The findings provide new incites for IPV prevention in Lagos with implications for further research.
Keywords: Intimate partner violence; Women; Nigeria; Prevalence; Risk factors